2022
DOI: 10.3390/ijerph19137895
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Psychosocial Factors of Suicide Decedents and Survivor of Suicide Loss: Psychological Autopsy Study of Incheon City in South Korea

Abstract: In South Korea, the suicide rate is more than double the OECD average, and precise identification of the cause is required for suicide prevention. Psychological autopsy is used to reveal factors related to suicidal behavior; however, such studies are lacking in Korea. This study investigated the factors related to suicide using psychological autopsies in Incheon, a major city in Korea. In total, 46 cases were investigated using the Korea-Psychological Autopsy Checklist (K-PAC), and data on mental health condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 38 publications
(36 reference statements)
0
1
0
9
Order By: Relevance
“…Korea mempelajari cara penanganan dari Firlandia yang terbukti dapat menganalisis dengan cermat akar penyebab kematian bunuh diri nasional dan regional. Di Finlandia, berbagai saran kebijakan dan layanan untuk mengurangi kematian akibat bunuh diri telah dikembangkan dengan menggunakan hasil autopsi psikologis, Hakanaen dalam (Bae et al, 2022a). Karena bunuh diri dianggap dapat dicegah, pemerintah mencari metode yang paling efektif yaitu melakukan autopsi psikologis Keith dan Kees dalam (Bae et al, 2022a).…”
Section: Latar Belakangunclassified
See 3 more Smart Citations
“…Korea mempelajari cara penanganan dari Firlandia yang terbukti dapat menganalisis dengan cermat akar penyebab kematian bunuh diri nasional dan regional. Di Finlandia, berbagai saran kebijakan dan layanan untuk mengurangi kematian akibat bunuh diri telah dikembangkan dengan menggunakan hasil autopsi psikologis, Hakanaen dalam (Bae et al, 2022a). Karena bunuh diri dianggap dapat dicegah, pemerintah mencari metode yang paling efektif yaitu melakukan autopsi psikologis Keith dan Kees dalam (Bae et al, 2022a).…”
Section: Latar Belakangunclassified
“…Di Finlandia, berbagai saran kebijakan dan layanan untuk mengurangi kematian akibat bunuh diri telah dikembangkan dengan menggunakan hasil autopsi psikologis, Hakanaen dalam (Bae et al, 2022a). Karena bunuh diri dianggap dapat dicegah, pemerintah mencari metode yang paling efektif yaitu melakukan autopsi psikologis Keith dan Kees dalam (Bae et al, 2022a). Autopsi psikologis adalah prosedur untuk memperkirakan penyebab bunuh diri dengan memeriksa perilaku psikologis dan perubahan orang yang meninggal bunuh diri selama periode tertentu sebelum kematian melalui pernyataan orang yang mengenal individu dan catatan yang terkait dengannya (Shneidman, 2004).…”
Section: Latar Belakangunclassified
See 2 more Smart Citations
“…Studies have reported that suicide survivors have more risk factors for their emotional health, and are more vulnerable to emotional distress and psychopathology such as depression, post-traumatic stress disorder, complicated grief, and even suicidal ideation and behavior [ 15 , 16 ]. In research where psychological autopsies and interviews with survivors have been conducted, mental-health problems have been identified before and after the death of the individual in more than half of their families, as well as many cases of attempted and completed suicide among survivors, which may be associated with genetic factors, stressors, and shared environments, with the conclusion that survivors are at high risk for suicide [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%